To the issue of the perfection of anti-corruption legislation (Journal of actual problems of jurisprudence, 2019)
This article focuses on the improvement of anti-corruption legislation in the light of the leading mandatory independent anti-corruption expertise of draft laws and regulations.In this paper the authors present a valid conclusion about the need to consider the opinions of experts in making the law and monitor the implementation of anti-corruption expert groups proposals made during the preparation of draft legal acts.Key words: anti-corruption legislation, anti-corruption expertise, draft legal acts, anti-corruption strategy.